Effectiveness of workplace health promotion programs for industrial workers: a systematic review - Sasha Javanmardi; Ludwig Rappelt; Sascha Zangenberg; Lars Heinke; Christian Baumgart; Daniel Niederer; Jürgen Freiwald (BMC Public Health)
Abstract Background Workplace health promotion is essential for individual and organisational well-being and disease prevention, also in industrial workers. As the transfer of the evidence on the effectiveness of such programs into practice is limited due to scattered effects, the need for a consolidation of the available studies is given. The purpose of this systematic review was to synthesise the evidence on the effectiveness of workplace health promotion programs for industrial workers. Methods An electronic literature search was conducted in PubMed, Cochrane Library, Web of Science™, Scopus, and EBSCOHost until July 26th 2023. Studies investigated industrial workers who performed manual labour for at least 20 h per week were included. They had to receive a workplace health promotion intervention under any control condition. Outcomes were workplace health interventions’ safety and corresponding health-related outcomes. The revised Cochrane risk-of-bias assessed the risk of bias (Rob 2) tool for randomised control trials (RCT) and cluster RCT. Quality assessment was performed using a modified Downs and Black Checklist. Results Of the 25,555 studies initially identified, 39 were included. Generally, the mean quality of the studies was moderate, with most studies judged with a high overall risk of bias. Twenty-seven studies employed a behavioural approach, while one study adopted an organisational one. Ten studies utilised a multicomponent approach, and one intervention improved safety outcomes. The analysis of the results indicated an overall positive but heterogeneous effect across the different approaches. Conclusions The studies included in this review provide evidence that workplace health promotion can be effective. However, the overall findings are inconclusive due to the high risk of bias. Therefore, the results should be interpreted cautiously. Despite the considerable amount of research conducted in this field, additional well-designed studies are needed to fully confirm the effectiveness and determine the most promising types of interventions for improving and maintaining industrial health.